THE USE OF ENGLISH MOVIE IN TEACHING AUSTINâS ACT - Kayyis, Rahmatika (JURNAL SMART, 2016)
The purpose of this research is to investigate and describe the finding about the use of English movie in teaching Austinâs act in the fifth semester. This research is categorized as descriptive qualitative research. It means that the writer would describe the data gain as naturally as possible. The writer used this method in order to get specific, factual, and meaningful data. In this research, the writer used observation, interview, and documentation to collect the data. The population of the research was the students of fifth semester of STKIP Muhammadiyah Pringsewu Lampung in the academic year of 2014/2015. The writer could conclude that the use of English movie in teaching Austinâs act has good response. the use of movie in teaching Austinâs act based on attention and particioation reached âgoodâ scale.Keywords: Austinâs act, English movie, descriptive qualitative